Understanding inequalities stratification and difference - Platt, Lucinda (Cambridge, [England] Polity Press, 2019)
"Bringing together the most recent empirical evidence and the latest theoretical debates, this fully revised new edition gets to grips with a broad range of inequalities in people's lives. Examining social class, gender, ethnicity, disability and migration status, it demonstrates how these play out in relation to education, health, poverty, neighbourhood and housing, and how they cumulate across the life course. Richly illustrated with figures and concrete examples showing the distribution of life chances across social groups, the book shows how people's lives are structured by inequalities across multiple dimensions. Comprehensive topical chapters are framed by an exploration of the meaning and interpretation of inequalities and a discussion highlighting the important intersections between them. With new chapters on disability and on international migration, this new edition continues to provide a wide-ranging but detailed and theoretically sophisticated account of contemporary inequalities that will be invaluable to undergraduate and masters students alike"--Provided by publisher.
"Bringing together the most recent empirical evidence and the latest theoretical debates, this fully revised new edition gets to grips with a broad range of inequalities in people's lives. It continues to provide a wide-ranging but detailed account of contemporary inequalities that will be invaluable to undergraduate and masters students alike"--Provided by publisher.
Chapter 1: Introduction -- Part 1 -- Chapter 2: Class -- Chapter 3: Gender -- Chapter 4: Ethnicity -- Chapter 5: International migration -- Chapter 6: Disability -- Part 2 -- Chapter 7: Age and the life course -- Chapter 8: Education -- Chapter 9: Income, wealth and poverty -- Chapter 10: Health -- Chapter 11: Neighbourhood and housing -- Chapter 12: Conclusions: Inequality, Intersectionality and Diversity.
Revised edition of the author's Understanding inequalities, 2011.
Includes bibliographical references (pages 295-339) and index.
Keywords: Equality -- Great Britain; Social stratification -- Great Britain